2015
DOI: 10.3791/52677
|View full text |Cite
|
Sign up to set email alerts
|

Testing Sensory and Multisensory Function in Children with Autism Spectrum Disorder

Abstract: In addition to impairments in social communication and the presence of restricted interests and repetitive behaviors, deficits in sensory processing are now recognized as a core symptom in autism spectrum disorder (ASD). Our ability to perceive and interact with the external world is rooted in sensory processing. For example, listening to a conversation entails processing the auditory cues coming from the speaker (speech content, prosody, syntax) as well as the associated visual information (facial expressions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
0
13
0
2
Order By: Relevance
“…For example, the ability to benefit from seeing an speaker's face while conversing in a noisy environment is dependent upon the effectiveness of the auditory signal, but individuals with schizophrenia (Ross, Saint-Amour, Leavitt, Molholm, et al, 2007) and autism (Foxe, et al, 2013) show deficits in the amount of perceptual benefit they gain at low levels of stimulus effectiveness. Furthermore, dysfunction in temporal processing of multisensory stimuli have also been shown in individuals with autism (Baum, Stevenson, & Wallace, 2015; Bebko, Weiss, Demark, & Gomez, 2006; de Boer-Schellekens, Eussen, & Vroomen, 2013; Foss-Feig, et al, 2010; Kwakye, Foss-Feig, Cascio, Stone, & Wallace, 2011; Stevenson, Segers, Ferber, Barense, & Wallace, 2014; Stevenson, Siemann, Schneider, et al., 2014; Stevenson, Siemann, Woynaroski, et al, 2014a, 2014b; Wallace & Stevenson, 2014; Woynaroski, et al, 2013), schizophrenia (Martin, Giersch, Huron, & van Wassenhove, 2013), and dyslexia (Froyen, Willems, & Blomert, 2011; Hairston, Burdette, Flowers, Wood, & Wallace, 2005b; Virsu, Lahti-Nuuttila, & Laasonen, 2003). Since having an appropriately sized temporal binding window ensures proper multisensory integration, one avenue of future research should investigate whether or not clinical populations with enlarged temporal windows will show a corresponding widening of these windows with changing stimulus properties (i.e., stimulus intensities as described in the current study) or with increasing levels of stimulus complexity (Stevenson & Wallace, 2013; Vroomen & Stekelenburg, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the ability to benefit from seeing an speaker's face while conversing in a noisy environment is dependent upon the effectiveness of the auditory signal, but individuals with schizophrenia (Ross, Saint-Amour, Leavitt, Molholm, et al, 2007) and autism (Foxe, et al, 2013) show deficits in the amount of perceptual benefit they gain at low levels of stimulus effectiveness. Furthermore, dysfunction in temporal processing of multisensory stimuli have also been shown in individuals with autism (Baum, Stevenson, & Wallace, 2015; Bebko, Weiss, Demark, & Gomez, 2006; de Boer-Schellekens, Eussen, & Vroomen, 2013; Foss-Feig, et al, 2010; Kwakye, Foss-Feig, Cascio, Stone, & Wallace, 2011; Stevenson, Segers, Ferber, Barense, & Wallace, 2014; Stevenson, Siemann, Schneider, et al., 2014; Stevenson, Siemann, Woynaroski, et al, 2014a, 2014b; Wallace & Stevenson, 2014; Woynaroski, et al, 2013), schizophrenia (Martin, Giersch, Huron, & van Wassenhove, 2013), and dyslexia (Froyen, Willems, & Blomert, 2011; Hairston, Burdette, Flowers, Wood, & Wallace, 2005b; Virsu, Lahti-Nuuttila, & Laasonen, 2003). Since having an appropriately sized temporal binding window ensures proper multisensory integration, one avenue of future research should investigate whether or not clinical populations with enlarged temporal windows will show a corresponding widening of these windows with changing stimulus properties (i.e., stimulus intensities as described in the current study) or with increasing levels of stimulus complexity (Stevenson & Wallace, 2013; Vroomen & Stekelenburg, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, individuals with diagnoses of ASD and SZ performed an audiovisual speech simultaneity judgment task (Baum et al ., ). In addition to the standard analysis entailing fitting these data with a Gaussian function and deriving the TBW (Van der Burg et al ., ; Noel et al ., ; Simon et al ., ), we applied a Bayesian causal inference model to the data (Kording et al ., ; Shams & Beierholm, ).…”
Section: Introductionmentioning
confidence: 97%
“…Surprisingly, the groups did not differ in either the simple flash-beep condition or the tool condition. However, individuals with ASD showed decreased temporal acuity in the speech task, meaning that they needed longer stimulus-onset asynchronies (SOAs) to recognize asynchronous onsets than controls (see also Baum et al 2015b). Stevenson et al (2014a) also found that the width of the TBW measured in the flash beep, tool, and speech tasks correlated with the strength of the McGurk effect (McGurk and MacDonald 1976) in the ASD but not the TD group.…”
Section: Discrepancies Between Temporal Binding Window Studies In Asdmentioning
confidence: 97%